The Demand for Heterogeneous Capital and Labour Inputs in a Developing Economy (The Pakistan Development Review, 1986)
By using translog cost function this paper examines the structure of production of India's manufacturing sector when heterogeneous labour and capital are employed. It concludes that (a) machinery, equipment and structures are substitutable for different types of labour; (b) non-production workers work more intensively with machines and equipment than production workers in most of the manufacturing industries; (c) non-production workers are substitutable for production workers; and (d) non-production and production workers must be treated as separate labour inputs in production, and machinery and equipment and structures should be treated as separate capital inputs.